Hostile relationships in social work practice: anxiety, hate and conflict in long-term work with involuntary service users. Issue 1 (2nd January 2021) - Ferguson, Harry; Disney, Tom; Warwick, Lisa; Leigh, Jadwiga; Cooner, Tarsem Singh; Beddoe, Liz
ABSTRACT: While recognition that some service users do not want social work involvement has grown in recent years, little research has explored what relationships between social workers and 'involuntary clients' look and feel like in practice and how they are conducted in real time. This paper draws from research that observed long-term social work practice in child protection and shows how relationships based on mutual suspicion and even hate were sustained over the course of a year, or broke down. Drawing on a range of psycho-social theories, the paper adds to the literature on relationship-based practice by developing the concept of a 'hostile relationship'. The findings show how hostile relationships were enacted through conflict and resistance – especially on home visits – and how anxiety and other intense feelings were often avoided by individuals and organisations. Much more needs to be done to help social workers recognise and tolerate hostility and hate, to not retaliate and to enact compassion and care towards service users.